Postoperative cognitive change after cardiac surgery predicts long‐term cognitive outcome. Issue 9 (17th July 2020) - Relander, Kristiina; Hietanen, Marja; Rantanen, Kirsi; Rämö, Juhani; Vento, Antti; Saastamoinen, Kari‐Pekka; Roine, Risto O.; Soinne, Lauri
Abstract: Objectives: Postoperative cognitive dysfunction (POCD) is a common consequence of coronary artery bypass grafting. However, domain‐specific associations between postoperative changes and long‐term performance are poorly known. The aim of this study was to investigate whether domain‐specific cognitive changes after cardiac surgery predict long‐term cognitive outcome. Materials and Methods: We assessed 100 patients (86 men, mean age 60) before coronary artery bypass grafting, with re‐examinations after one week, three months, and a mean of 6.7 years. The extensive neuropsychological test battery was organized into seven functional cognitive domains. Cognitive decline and improvement were defined with the reliable change index derived from 17 matching healthy controls. Analyses were adjusted for baseline cognitive performance, age, gender, education and cardiovascular risks factors. Results: On group level, one week after surgery 71% patients showed cognitive decline and 9% improvement in any functional domain, as compared to preoperative results. Three months postsurgery, decline was observed in 47% and improvement in 25% of patients. Executive functioning was the most sensitive domain to both decline and improvement. Postoperative dysfunction predicted long‐term cognitive deterioration six years after operation, particularly in the domain of executive functioning. Conclusions: POCD after coronary artery bypass grafting is an essential risk factor for long‐term deterioration and an indication for neuropsychological follow‐up. Assessment of change in executive functioning after coronary artery bypass grafting may help to identify patients at risk for unfavorable long‐term outcome. Abstract : The aim of this study was to investigate whether domain‐specific cognitive changes after cardiac surgery predict long‐term cognitive outcome. We assessed 100 patients before coronary artery bypass grafting, with re‐examinations after one week, three months, and six years. Postoperative dysfunction predicted long‐term cognitive deterioration six years after operation, particularly in the domain of executive functioning.